Discovery of polymethoxylated flavonoids in Artemisia argyi as main active components in inhibiting rice blast fungus - Jia Zhou; Yunhan Wang; Qiaohuan Chen; Jinxin Li; Rong Xu; Bei Wang; Dahui Liu; Yuhuan Miao (Chemical and Biological Technologies in Agriculture)
Abstract Background Rice blast is a devastating disease caused by Magnaporthe grisea, and it is not well controlled globally. As a Traditional Chinese Medicine, Artemisia argyi has been proven to have inhibitory effects on a variety of phytopathogenic fungi. Here, we used bioactivity-guided isolation method and transcriptomics to clarify the antifungal active compounds in A. argyi and their antifungal mechanisms. Results In vitro studies showed that the absolute ethanol extract (AEE) of A. argyi had a strong inhibitory effect on the growth of M. grisea, with a low EC50 value of 1.156 mg/mL, and could cause the destruction of hyphae cell membrane and the leakage of cell contents. To identify the active constituents, we fractionated the AEE using macroporous adsorption resin and silica gel column chromatography. The active fraction (Fr.F-1) was fractionated and had even higher antifungal activity than AEE. The results showed that both AEE and Fr.F-1 could impact primary metabolic pathways and reactive oxygen species homeostasis of M. grisea, decrease the content of reducing sugars and downregulate the expression of genes related to starch and sucrose metabolism. Further fractionation of Fr.F-1 led to the identification of two polymethoxylated flavonoids (eupatilin and 3,5,3ʹ-trihydroxy-7,8,4ʹ-trimethoxyflavone), both of which had antifungal activity and they worked synergistically in Fr.F-1. Finally, we also investigated the effect of AEE, Fr.F-1 and eupatilin on rice blast control. The results showed that AEE, Fr.F-1 and eupatilin application strongly enhanced rice resistance to M. grisea. Conclusion In brief, these findings indicate that Fr.F-1 subfraction from A. argyi and its main components polymethoxylated flavonoids confer inhibiting activities to M. grisea. This discovery can effectively alleviate the degradation pressure of A. argyi by-products, promote the healthy development of its industry, and provide new a strategy for the development of new botanical fungicides to control rice blast. Graphical Abstract